Policy Advocacy on Public Services of Difabelity People in Balikpapan City - Anissa Putri Mulia; Irwan Noor; Abdullah Said (Sekolah Pascasarjana Universitas Brawijaya, 2019)
Analyze policy advocacy on public services for persons with disabilities in the city of Balikpapan as a form of protection to social disabilities. The author analyzes the public services of persons with disabilities using 3 (three) components, including the Agenda Setting, Problem Definition, and Policy Design that should have been chosen by the Balikpapan City Government in resolving the Diffability Problem. The type of research used is descriptive research with a qualitative approach. The results showed that policy advocacy on public services for persons with disabilities in the city of Balikpapan was seen from 3 (three) activities, namely the Agenda Setting activities carried out in the Formulation of Policy Advocates assessed by the Balikpapan City Government were not good (not optimal). Policy Definition of People with Disabilities in Balikpapan City in the framework of Social Protection Against Diffability is considered to have carried out forecasting needs, but is still not optimal. The Balikpapan City Government has taken several alternative policies, namely to gradually develop facilities and infrastructure for the convenience of difabelitas in Balikpapan City. Policy Design Activities Problems with Disability that should have been taken by the Balikpapan City Government, include a